Accuracy of BLE systems in the H&S improvement aspects in construction. (2017) - Nowotarski, Piotr; Pasławski, Jerzy; Mielcarek, Dawid
Abstract: Health and safety is one of the most important issue when it comes to the construction industry. At all stages of construction workers are at risk of accidents and serious injury. There are many solutions that tries to address the problems of H&S on the construction sites with different level of their complexity. One of the technology that can be successfully used to improve this part is BLE beacons technology. This technology has been improved recently and provides variety of convenience services. Authors of this work decided to examine Bluetooth devices and performed range test on the devices received from one of the European Beacon producers. Beacons are based on Bluetooth Low Energy (BLE) which is a medium ranged transmission standard aiming for cheaper devices with longer lasting batteries. The main purpose of this article is to present the result of the tests performed in the open area for the purpose of future precise use at the construction site in improving general level of H&S and propose recommendations for further use of BLE devices in construction industry.